The contemporary medieval in practice - Lees, Clare A. (Spotlights (UCL Press), 2019)
The Contemporary Medieval in Practice looks at early medieval British culture, often termed Anglo-Saxon Studies (c. 500-1100), and its relation with, use of, and re-working in contemporary visual, poetic, and material culture (after 1950).